Ukraine Water Supply and Sanitation Policy Note : Toward Improved, Inclusive, and Sustainable Water Supply and Sanitation Services - World Bank (World Bank, Washington, DC, 2021)
This policy note outlines key challenges and identifies specific recommendations for improved, inclusive, and sustainable development of Ukraine’s water supply and sanitation (WSS) sector, which is important for the health and well-being of the country’s people, the economy, and the environment. Water touches every aspect of development and is linked with nearly every Sustainable Development Goal (SDG). The issues facing the water sector, if not addressed, will affect other development agendas in Ukraine, such as food and energy security, jobs, equal access to services, and social inclusion, as well as adaptation to and mitigation of climate change. Like many other countries, the ongoing Coronavirus (COVID-19) pandemic has affected Ukraine by exacerbating problems in poor performing sectors and increasing inequalities by driving people into poverty. The situation calls for integrated solutions to reverse that impact through greener, more resilient, and inclusive sustainable development. This WSS Policy Note aims to outline key challenges in the Ukrainian WSS sector and to recommend needed reforms toward sustainable WSS service provision to policy makers.